Selection of novel reference genes for use in the human central nervous system: a BrainNet Europe Study - Durrenberger, Pascal F.; Gebicke-Härter, Peter J. (Acta neuropathologica, 2012)
The use of an appropriate reference gene to ensure accurate normalisation is crucial for the correct quantification of gene expression using qPCR assays and RNA arrays. The main criterion for a gene to qualify as a reference gene is a stable expression across various cell types and experimental settings. Several reference genes are commonly in use but more and more evidence reveals variations in their expression due to the presence of on-going neuropathological disease processes, raising doubts concerning their use. We conducted an analysis of genome-wide changes of gene expression in the human central nervous system (CNS) covering several neurological disorders and regions, including the spinal cord, and were able to identify a number of novel stable reference genes. We tested the stability of expression of eight novel (ATP5E, AARS, GAPVD1, CSNK2B, XPNPEP1, OSBP, NAT5 and DCTN2) and four more commonly used (BECN1, GAPDH, QARS and TUBB) reference genes in a smaller cohort using RT-qPCR. The most stable genes out of the 12 reference genes were tested as normaliser to validate increased levels of a target gene in CNS disease. We found that in human post-mortem tissue the novel reference genes, XPNPEP1 and AARS, were efficient in replicating microarray target gene expression levels and that XPNPEP1 was more efficient as a normaliser than BECN1, which has been shown to change in expression as a consequence of neuronal cell loss. We provide herein one more suitable novel reference gene, XPNPEP1, with no current neuroinflammatory or neurodegenerative associations that can be used for gene quantitative gene expression studies with human CNS post-mortem tissue and also suggest a list of potential other candidates. These data also emphasise the importance of organ/tissue-specific stably expressed genes as reference genes for RNA studies.